Efforts to Improve Writing Ability on Critical Thinking Concepts through the POE2WE Model - Ade Siti Haryanti; Sholeh Hidayat; Dase Erwin Juansah (Jurnal Pendidikan Indonesia Gemilang, 2024)
This research was motivated by the low ability to write arguments for 3rd-semester Indonesian and literature education students. This study aimed to improve students' argumentation writing skills on critical thinking concepts through the POE2WE learning model. This research used a class action research (CAR), which is planned to take place in 2 cycles, each containing four stages: planning, implementing actions, observation, and reflection. The research results on improving learning in the first cycle showed an increase in students' argumentation writing skills. The average score was 64.04 with sample presentations that passed 43.3% (before the cycle), 67.37 with sample presentations that passed 60% (after cycle I), and 75.8 for sample presentations that passed 100%.